Structural, mechanical and electronic properties of Zr2SeB MAX phase through DFT approach at ambient and elevated pressures (Bangladesh Journal of Scientific and Industrial Research, 2024)
The DFT approach has been used in the pressure range of 0 - 50 GPa to examine the physical characteristics of the synthesized MAX phases Zr2SeB for the first time. The calculated lattice parameters agree with previous findings at ambient pressure. The density of states and band structure exhibit that within the studied pressure range, Zr2SeB is metallic. Under various pressures, partial DOS is also taken into consideration. The investigated compound maintains their mechanical stability up to 50 GPa.  Zr2SeB is elastically anisotropic up to 50 GPa, and brittle up to 20 GPa pressure. The brittleness of the material decreases with increasing pressure. At 30, 40 and 50 GPa, however, Zr2SeB exhibit a ductile behavior. The MAX phase research community is anticipated to be inspired by this discovery to further investigate the properties of this material under various pressures.Bangladesh J. Sci. Ind. Res. 59(3), 129-138, 2024